Molecular characterization and SNP identification using genotyping-by-sequencing in high-yielding mutants of proso millet - Francis, Neethu; Rajasekaran, Ravikesavan; Rajagopalan, Veera Ranjani; Bakya, S. Vinothini; Muthurajan, Raveendran; Kumar, Ashwini Girish; Alagarswamy, Senthil; Krishnamoorthy, Iyanar; Thiyagarajan, Chitdeshwari (Frontiers in Plant Science, 2023)
Proso millet (Panicummiliaceum L.) is a short-duration C4 crop that is drought tolerant and nutritionally rich and can grow well in marginal lands. Though the crop has many climate-resilient traits like tolerance to drought and heat, its yield is lower than that of common cereals like rice, wheat, and maize. Being an underutilized crop, the molecular resources in the crop are limited. The main aim of the present study was to develop and characterize contrasting mutants for yield and generate functional genomic information for the trait in proso millet. Gamma irradiation-induced mutant population was screened to identify high-yielding mutants, which were evaluated up to M4 generation. One mutant with a dense panicle and high yield (ATL_hy) and one with a lax panicle and low yield (ATL_ly) along with the wild type were sequenced using the genotyping-by-sequencing approach. The variants detected as single nucleotide polymorphisms (SNPs) and insertions–deletions (InDels) were annotated against the reference genome of proso millet. Bioinformatic analyses using the National Center for Biotechnology Information (NCBI) and UniProt databases were performed to elucidate genetic information related to the SNP variations. A total of 25,901, 30,335, and 31,488 SNPs, respectively, were detected in the wild type, ATL_hy mutants, and ATL_ly mutants. The total number of functional SNPs identified in high-yielding and low-yielding mutants was 84 and 171, respectively. Two functional SNPs in the high-yielding mutant (ATL_hy) and one in the low-yielding mutant (ATL_ly) corresponded to the gene coding for “E3 ubiquitin-protein ligase UPL7”. Pathway mapping of the functional SNPs identified that two SNPs in ATL_ly were involved in the starch biosynthetic pathway coding for the starch synthase enzyme. This information can be further used in identifying genes responsible for various metabolic processes in proso millet and in designing useful genetic markers.